2009
DOI: 10.1159/000236447
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonic Acid Supplementation Decreases P300 Latency and Increases P300 Amplitude of Event-Related Potentials in Healthy Elderly Men

Abstract: In the present study, we examined the effects of arachidonic acid (ARA) on age-related event-related potential (ERP) changes in 25 healthy elderly men. This study was performed using a double-blind crossover design. The subjects were administered 600 mg/day of ARA-enriched triglyceride (SUNTGA40S; containing 240 mg ARA) in capsules or the same amount of olive oil in capsules as an inactive placebo for 1 month. ERPs were measured before capsule administration and after 1 month of administration, and P300 latenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 40 publications
2
32
0
Order By: Relevance
“…Previously, we reported that ARA-enriched TAG supplementation significantly improved cognitive function regarding P300 components correlated with age in adults 12 . Based on the results of the present study, we suggest that low serum ARA levels are associated with a decrease in P300 components in elderly men stratified by baseline serum ARA levels.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…Previously, we reported that ARA-enriched TAG supplementation significantly improved cognitive function regarding P300 components correlated with age in adults 12 . Based on the results of the present study, we suggest that low serum ARA levels are associated with a decrease in P300 components in elderly men stratified by baseline serum ARA levels.…”
Section: Discussionmentioning
confidence: 83%
“…P300 latency was positively correlated with age in adults, and P300 amplitude generally lowered with age 14,15 . We found that ARA-enriched TAG supplementation significantly shortened P300 latency and increased P300 amplitude, accompanied by an increase in ARA levels in serum phospholipids and unchanged DHA content 12 . Thus, ARA-enriched TAG supplementation may improve age-related decreases in cognitive function in healthy elderly participants.…”
mentioning
confidence: 69%
See 3 more Smart Citations